PEMBELAJARAN BAHASA ARAB AL-QUR’AN TINGKAT DASAR - Ulum, Moh Samsul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
The basic Quran teaching-learning process has two important phases; The capability to read and the capability to understand the tenses. There are five points to learn Quran ; 1. Introducing the alphabeth( hijaiyah Makhraj), 2. The tenses- mark, 3.The alphabeth combination, 4. The rule of tajwed and its sub topic, 5.Irreguler reading-rule. In order to achieve the Quran skill some ways could be applied such as reading-drill, vocabulary skill and using pictures as a media to support the learning process. Reviewing previous topic also important to find the students improvement. Keyword: Quran teaching, and students